A study of Holocene Asian summer and winter monsoon change by an analog of climate factors between millennial and modern interannual scales. (June 2020) - Li, Yu; Li, Yichan; Ye, Wangting; Peng, Simin
The East Asian monsoon exerts a profound influence on environmental change in the East Asian region. Various factors have been hypothesized as the dominant Asian monsoon forcings, however, the forcings can change from interannual to millennial timescales. The linkages between monsoon forcings at different timescales remain unclear. To better understand the connection of the variabilities and mechanisms of the East Asian monsoon at various timescales, we present a modern analog. Various climatic data, monsoon indices, and circulation factor calculations were used to identify the variabilities and controlling factors of the modern East Asian summer and winter monsoons. Paleo-climatic proxies from a region sensitive to both summer and winter monsoons were used in concert with monsoon simulation data to reconstruct and analyze paleo-monsoon variations and mechanisms. Results showed that the weakening of the Holocene Asian summer and winter monsoons is closely linked to low-latitude summer insolation and mid-latitude winter insolation, while modern summer and winter monsoons are related to global circulation, sea surface temperature, and sea ice change. We confirm that the driving mechanism of the monsoon was dependent on timescale.